Uric Acid and Diabetic Retinopathy: A Systematic Review and Meta-Analysis - Guo, Yicong; Liu, Siyue; Xu, Huilan (Frontiers in Public Health, 2022)
Objective: The relationship between uric acid (UA) and diabetic retinopathy (DR) remains ambiguous, and results of current studies on the uric acid levels in patients with DR were conflicting. A meta-analysis was performed to provide a better understanding of the relationship between uric acid and DR. Methods: PubMed, Web of Science, Embase, and the Cochrane Library databases were searched until December 11, 2021 to identify eligible studies, which compared the uric acid levels of case group (DR patients) and control group (diabetic controls and healthy subjects). Weighted mean difference (WMD) with a 95% confidence interval (CI) was used to evaluate the difference in uric acid levels between case group and control group. Results: Twenty-one studies involving 4340 DR patients and 8595 controls (containing 8029 diabetic controls and 566 healthy subjects) were included in this meta-analysis. We found DR patients had statistically significantly higher levels of uric acid compared with diabetic controls (WMD = 36.28; 95% CI: 15.68, 56.89; P< 0.001) and healthy subjects (WMD = 70.80; 95% CI: 19.85, 121.75; P = 0.006). An obvious heterogeneity existed among the 21 studies (I2 = 97%, P< 0.001). Subgroup analyses of different phases of DR showed that uric acid levels were increased significantly in subjects with PDR (WMD = 46.57; 95% CI: 28.51, 64.63; P< 0.001) compared with diabetic controls, but not in NPDR (WMD = 22.50; 95% CI: -6.07, 51.08; P = 0.123). In addition, uric acid levels were more increased in subjects with BMI ≥ 25.0 kg/m2 and over 15 years of diabetes. Univariate meta-regression analysis revealed body mass index (BMI) (P = 0.007, Adj R2 = 40.12%) and fasting blood glucose (FBG) (P = 0.040, Adj R2 = 29.72%) contributed to between-study heterogeneity. Conclusion: In conclusion, our study supports the current evidence that patients with DR (especially PDR) have higher levels of uric acid compared with diabetic controls. Increased uric acid levels may be a potential risk factor for the onset and progression of DR in diabetic patients, and worth to be considered as a biomarker for prediction.